Sandal in Bundelkhand Forest Division, Uttar Pradesh - Sinha, R. L. (Indian Forester, 1961)
The note describes the occurrence of sandal wood (Santalum album) in the forest reserves of Bundelkhand forest division, district Jhansi (U.P.), the characteristics of the tract, composition of the forest crop and injuries to which it is liable. It deals with the stocking, result of enumeration of sandal crop and present management of sandal wood area, gives yield figures of oil from Bundelkhand sandalwood as compared to the yield from other sandalwood regions, and discusses in brief the work done so far as regards its reproduction both natural and artificial. It concludes with a discussion on natural habitat of sandalwood vis-a-vis its occurrence in Bundelkhand tract, its further extension and future ,management.